Analysis of Multiple Intelligences in Arabiyah Baina Yadaik Book - Mu'awanah, Elyatul; Insani, Razik (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to describe the analysis of multiple intelligences in the book 'Arabiyah Baina Yadaik. The research approach is qualitative, specifically library research. The analysis technique used is content analysis. The content analysis used is a qualitative content analysis approach. The data collection process is a literature study analysis of the book by reviewing learning materials and practice questions, analyzing the suitability of the book with aspects of multiple intelligences, then describing the results of the analysis and providing conclusions with suggestions. Based on the results of the research, the distribution of multiple intelligence aspects in the book is still uneven. Analysis of learning activities, materials, and practice questions in the book shows the highest intelligence is linguistic intelligence. The middle intelligence category includes spatial, interpersonal, and logical-mathematical intelligence. The lowest intelligence mentioned is existential intelligence. The book does not mention intrapersonal, kinesthetic, musical, or naturalistic intelligences at all. The four intelligences not mentioned in the book can be raised and developed by a teacher through learning activities in the classroom and outside the classroom with various methods, strategies, and more intriguing learning models.